Rohingya in Aceh: Human Rights Vs Security Justice Islamic Law Perspective - Any Ismayawati; Inna Fauziatal Ngazizah; Saidatul Nadia Abd Aziz (Jurnal Pembangunan Hukum Indonesia, 2025)
The humanitarian crisis affecting the Rohingya ethnic group has driven thousands of asylum seekers to Southeast Asia, including Aceh Province, where the majority of the population is Muslim and Sharia law is applied. This situation raises important issues regarding the protection of human rights for both the Muslim community in Aceh and Rohingya asylum seekers. The purpose of this study is to analyse the Islamic legal perspective on human rights protection in Aceh and to examine the dilemma between security and humanity in the handling of Rohingya refugees. The method used is descriptive qualitative study with a normative-sociological approach through analysis of literature, Aceh sharia regulations, and international and national human rights documents. The results of the study show that Islamic legal principles, such as hifz al-nafs and hifz al-insaniyyah, provide a strong basis for the acceptance and protection of refugees. However, their implementation faces challenges in the form of social resistance, limited facilities, and concerns about local security disturbances. The conclusion that can be drawn is that human rights protection in Aceh can only be effective if there is harmonisation between Sharia values, security policies, and humanitarian commitments through the synergy of the government, religious scholars, and the community.